2002
DOI: 10.1128/jvi.76.11.5654-5666.2002
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Infection of Human Airway Epithelial Cells Is Polarized, Specific to Ciliated Cells, and without Obvious Cytopathology

Abstract: Gene therapy for cystic fibrosis (CF) lung disease requires efficient gene transfer to airway epithelial cells after intralumenal delivery. Most gene transfer vectors so far tested have not provided the efficiency required. Although human respiratory syncytial virus (RSV), a common respiratory virus, is known to infect the respiratory epithelium, the mechanism of infection and the epithelial cell type targeted by RSV have not been determined. We have utilized human primary airway epithelial cell cultures that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

79
519
7
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 512 publications
(610 citation statements)
references
References 40 publications
79
519
7
5
Order By: Relevance
“…This suggests a tropism for cells of the distal airway, and more homogeneous cell populations in lower airways. As expected, 13 ciliated cells are infected, and it appears that nonciliated cells are also infected as noted in an adenoid organ culture model. 14 Basal cells appear to distinctly be not infected (Figure 1a).…”
Section: Discussionsupporting
confidence: 79%
“…This suggests a tropism for cells of the distal airway, and more homogeneous cell populations in lower airways. As expected, 13 ciliated cells are infected, and it appears that nonciliated cells are also infected as noted in an adenoid organ culture model. 14 Basal cells appear to distinctly be not infected (Figure 1a).…”
Section: Discussionsupporting
confidence: 79%
“…Our results suggest that aMPV infection takes place at the apical region of the epithelium, which is comparable to the observations made after RSV infection of human nasal, tracheobronchial and bronchiolar airway epithelial cells (Zhang et al, 2002). Cilia may allow the virus to attach and therefore it may be suggested that polarized epithelial cells are the main target cells of aMPV (Jones et al, 1986;O'Loan & Allan, 1990;Majó et al, 1995;Jirjis et al, 2001;Zhang et al, 2002). In the present state of knowledge, the oviduct epithelium is the only other surface susceptible to aMPV, apart from respiratory epithelia (Jones et al, 1988).…”
Section: Discussionsupporting
confidence: 77%
“…A similar observation was seen in one study case of RSV infection of respiratory epithelial cells showing loss of ciliary activity without apoptotic signs (Domachowske et al, 2001). The tissue damage after RSV infection is suggested to be due to other destructive immune responses, induced to control virus replication (Zhang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…RSV replicates in these cells with relatively little evidence of cytopathology, contrary to the extensive morphologic changes observed in infected nonpolarized epithelial cell lines, such as HEp-2 cells. Furthermore, RSV infection is limited to the most superficial layer of ex vivo cultured stratified human respiratory epithelium (11). These findings are consistent with many clinical aspects of RSV infection.…”
supporting
confidence: 74%
“…In vitro and ex vivo studies have shown that the virus exhibits a preference for apical budding from infected, polarized epithelial cells (10,11). RSV replicates in these cells with relatively little evidence of cytopathology, contrary to the extensive morphologic changes observed in infected nonpolarized epithelial cell lines, such as HEp-2 cells.…”
mentioning
confidence: 99%